Red Cell Alloantibodies in Multi - Transfused Patients of Beta Thalassaemia Major - Madeeha Rehan ,Atifa Shuaib ,Lubna Zafar, (Journal of Rawalpindi Medical College, 2015)
Background: To study the frequency and specificity of various red cell alloantibodies in multi- transfused patients of beta thalassaemia major. Methods: In this comparative study two hundred diagnosed cases of Beta Thalassemia Major , of all ages and both genders, who received at least ten blood transfusions, were included .Patients with known alloantibodies, or with known autoimmune diseases,patients with known renal or liver disorders and with viral infections were excluded.Five ml venous blood was taken in a clear glass tube. Sera were separated and blood grouping and direct and indirect anti-globulin tests were performed on all samples. Samples positive for indirect anti-globulin test were stored in aliquots at -20 °C, till the tests were performed in batches. After thawing, antibody screening and antibody identification tests were performed in batches of ten on all indirect anti-globulin test (IAT) positive samples employing 11 cell panel of DIA-MED using standardized blood bank methods. All the results were recorded.The alloantibodies detected and their specificity was determined. Results: Out of 200 patients six patients (3%) were diagnosed to have alloantibodies which belonged to Rh system i.e. Anti-E and Anti-D. Conclusion:Rate of alloimmunization is low in our setup in multi- transfused patients of beta thalassaemia major. The most common alloantibody found in our patients is Anti-E.